Pengaruh Model Contextual Teaching and Learning Terhadap Keterampilan Berbahasa Peserta Pelatihan di LKP Rose Gumukmas - Dini Dwi Anggraini (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study sought to ascertain how the Contextual Teaching and Learning (CTL) approach affected the training participants' language proficiency at LKP Rose Gumukmas. Some training participants found it challenging to comprehend and use English words in everyday conversations. This study employed an associative- causal research method in conjunction with a quantitative methodology. Thirty participants in the "Survival English" program made up the study population; all of them were chosen to be responders. Questionnaires and documentation were used for data collection, and SPSS was used for data analysis employing validity, reliability, and normalcy checks in addition to basic linear regression analysis. The findings indicated that while the course participants' language proficiency fell into the "high" category, the application of the CTL model fell into the "very high" category. The results of the simple linear regression test showed a substantial impact of the CTL model on the language proficiency of course participants, with a significance level of 0.002 <0.05. The CTL model contributed 28.8% to the participants' language skills, whereas other factors outside the research had an impact on 71.2%, according to the coefficient of determination (R2) of 0.288. The language proficiency of participants at LKP ROSE Gumukmas is therefore positively and significantly impacted by the Contextual Teaching and Learning (CTL) methodology.
:: Finalisasi file repositori 23 Juli 2026_Kurnadi
Keywords: training; contextual teachind and learning; language proficiency